2022
DOI: 10.1186/s40478-022-01330-x
|View full text |Cite
|
Sign up to set email alerts
|

Tuberous sclerosis complex is a novel, amyloid-independent tauopathy associated with elevated phosphorylated 3R/4R tau aggregation

Abstract: Tuberous sclerosis complex (TSC) is a neurodevelopmental disorder caused by mutations in the TSC1 and TSC2 genes and autosomal dominantly inherited. These mutations cause hyperactivation of the mammalian Target of Rapamycin (mTOR) pathway, leading to the development of nonmalignant masses involving various organ systems. Patients with TSC also experience neuropsychiatric symptoms collectively termed Tuberous Sclerosis Complex Associated Neuropsychiatric Disorder (TAND). Due to research advancements in TSC, pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 14 publications
(15 reference statements)
1
15
0
Order By: Relevance
“…Assuming that the principles behind neurons are found, the initial function has been taken as an important tool for counting neurons, reasoning needs to be expressed as computation, and neural networks and M-P models were planned, starting to create neural networks (ANN) [11]. Liu, in his book "Society of Behavior," reported on Hebb synapse and Hebb law education, which laid the theoretical basis for the development of neural network algorithms [12].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Assuming that the principles behind neurons are found, the initial function has been taken as an important tool for counting neurons, reasoning needs to be expressed as computation, and neural networks and M-P models were planned, starting to create neural networks (ANN) [11]. Liu, in his book "Society of Behavior," reported on Hebb synapse and Hebb law education, which laid the theoretical basis for the development of neural network algorithms [12].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Liu et al proposed a target tracking algorithm, which uses the Meanshift as the core, and the feature representation method of the two-digit histogram is selected by using the color and gray information of the target image to represent the target model. At the same time, combined with the motion detection module, the key information is provided for the path planning, navigation, and other high-level decisions of the autonomous mobile robot in the indoor environment [ 5 ]. Mayandi et al built a robot sorting experimental system based on machine vision; in this system, the targets continuously enter the operation area the system controls the robot to achieve the object sorting, the system continuously and automatically obtains the image of the object through the camera, and the software analyzes the collected images, transforms the coordinates of target objects, identifies the classification information of target objects, and maintains the movement traces of sorting targets [ 6 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hyperphosphorylated and aggregated into neurofibrillary tangles (NFTs), Tau is a critical event in several neurodegenerative disorders, collectively known as tauopathies [ 48 , 90 , 102 ]. There is sufficient evidence to suggest implications of dysregulated mTOR signalling in MAP-Tau pathology observed in these neurodegenerative diseases [ 52 , 53 , 54 , 55 , 56 ]. More recent studies have shown that Tau protein pathology is also involved in several neurodevelopmental disorders, particularly those featuring hyperactivation of the mTOR pathway, including ASD [ 67 , 68 , 103 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with the study by Caccamo et al, who showed that genetically enhanced mTOR activity facilitated Tau pathology by elevating both endogenous Tau levels and phosphorylation in the hippocampi of the TSC2 heterozygous mice [ 53 ]. Liu et al described elevated levels of phosphorylated Tau in the cerebrospinal fluid of patients with TSC, suggesting that overstimulation of the mTOR pathway may be a novel, amyloid-independent tauopathy similar to that seen in AD [ 52 ]. Moreover, studies in vitro by Tang et al have reported that up-regulated mTOR promotes Tau dyshomeostasis by mediating the synthesis, phosphorylation, and aggregation of Tau.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation